THE PROBLEM OF CONSCIOUSNESS IN PHILOSOPHY (Western European Journal of Modern Experiments and Scientific Methods, 2024)
Philosophy of mind is a branch of philosophy that studies the nature and ontology of mind and its interaction with the body. The body-mind problem is a controversial issue in philosophy, but some disagreements about it have been resolved. This article provides an overview of the philosophical context of the problem of consciousness, its main aspects, and its relation to modern research. Philosophical thoughts and theories help to understand the nature of consciousness and its place in human life